2022
DOI: 10.3390/jcm11123283
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Plasminogen Activator Receptor (suPAR) in the Emergency Department (Ed): A Tool for the Assessment of Elderly Patients

Abstract: Emergency department (ED) overcrowding is a global issue setting challenges to all care providers. Elderly patients are frequent visitors of the ED and their risk stratification is demanding due to insufficient assessment methods. A prospective cohort study was conducted to determine the risk-predicting value of a prognostic biomarker, soluble urokinase plasminogen activator receptor (suPAR), in the ED, concentrating on elderly patients. SuPAR levels were determined as part of standard blood sampling of 1858 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
12
0
3
Order By: Relevance
“…The pooled analysis revealed a significant association between patients with high suPAR levels and length of hospital stay as compared to patients with low suPAR levels. It showed that patients with high suPAR levels stayed for a greater duration in the hospital as compared to patients with low suPAR levels (WMD = 2.82 days; 95% CI = 1.46-4.19; P < .0001; I 2 = 100%) as shown [21] Prospective Cohort Two Finnish hospital regions (Helsinki and Mikkeli) -High = >6 Low = <3 Holstein et al 2022 [32] Comparative Holstein et al 2022 [32] 330 in Supplementary Figure S5, http://links.lww.com/MD/K601. The exclusion of 1 study [21] was done to perform sensitivity analysis, however, it did not lead to a significant change in the heterogeneity of the included studies (Fig.…”
Section: Length Of Hospital Staymentioning
confidence: 89%
See 3 more Smart Citations
“…The pooled analysis revealed a significant association between patients with high suPAR levels and length of hospital stay as compared to patients with low suPAR levels. It showed that patients with high suPAR levels stayed for a greater duration in the hospital as compared to patients with low suPAR levels (WMD = 2.82 days; 95% CI = 1.46-4.19; P < .0001; I 2 = 100%) as shown [21] Prospective Cohort Two Finnish hospital regions (Helsinki and Mikkeli) -High = >6 Low = <3 Holstein et al 2022 [32] Comparative Holstein et al 2022 [32] 330 in Supplementary Figure S5, http://links.lww.com/MD/K601. The exclusion of 1 study [21] was done to perform sensitivity analysis, however, it did not lead to a significant change in the heterogeneity of the included studies (Fig.…”
Section: Length Of Hospital Staymentioning
confidence: 89%
“…After a full-text assessment of 43 articles for their eligibility, 30 articles were excluded which didn't meet the inclusion criteria. As a result, 13 studies [19,21,23,[27][28][29][30][31][32][33][34][35][36] were finalized to be included in this meta-analysis. A summary of the literature search is presented in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Un valor de suPAR > 6 ng/mL se asoció de manera independiente con mortalidad a 90 días y con mayor probabilidad de ingreso y de reconsulta, de forma similar a lo publicado por Holstein et al 22 , donde los pacientes con esos niveles tenían una mayor mortalidad. Esto apoyaría la hipótesis que este biomarcador aporta información pronóstica en los pacientes atendidos en urgencias, independientemente del país de pertenencia, y añade valor a otros aspectos que se usan de forma habitual.…”
Section: Discussionunclassified